ABSORPTIVE CAPABILITY AND INNOVATION IN BUREAUCRATIC ORGANIZATIONS: AN INSTITUTIONAL PERSPECTIVE IN SORONG CITY - purna, zarni adia; Ardiansyah, Faisal (Universitas Negeri Makassar, 2025)
The low level of innovation implementation within bureaucratic organizations in Sorong City is not directly proportional to the increasing reform budget allocated annually, indicating a fundamental problem in the organization's capacity to absorb and process external knowledge into concrete public service innovations. This study aims to analyze the relationship between absorptive capability and innovation within bureaucratic organizations in Sorong City from an institutional perspective. The study used a qualitative approach with a case study design in six regional government organizations, involving 18 informants selected through purposive sampling. Data were collected through in-depth interviews, non-participant observation, and documentation studies, then analyzed using six-stage thematic analysis. The results identified four main themes that form a layered causal system: limited knowledge acquisition, weak knowledge internalization, institutional barriers, and imbalances in human resource capacity as structural roots. These four themes operate as a system of mutually reinforcing barriers, where weaknesses in one dimension consistently exacerbate weaknesses in the others. Bureaucratic innovation in Sorong City is a systemic problem whose solution requires simultaneous intervention at the human capacity level, the institutional environment, and the organization's knowledge management mechanisms